Development of ecopedagogy in green campus educational book based on environmental pollution cases related to biology learning - Ichsan, Ilmi Zajuli; Sopiah, Sopiah; Ramdani, Akhmad Subkhi (Universitas Wiralodra, 2025)
Ecopedagogy education related to green campuses requires further innovation related to learning media. This study aims to develop a book on ecopedagogy education in a green campus based on environmental issues. The method of research and development in this study’s is based on the ADDIE approach with five stages. The first stage of this research is conduct an initial data analysis, which will be the basis for developing the Ecopedagogy. The second stage is design the educational media. The third stage is the development process and validation of media experts. The fourth stage is the implementation, and the last stage of developing this book media is to conduct an evaluation given by students; the form of an assessment of the book. This study’s results indicate that the ecopedagogy education media series on environmental issues on a green campus is categorized as very valid. Hence, it is suitable for use in learning activities. The results of this study indicate that the media series of ecopedagogy education can improve student learning outcomes based on the results of the pre-test and post-test. The development of learning media is essential to train students' skills in critical thinking. Suggestions for future research include implementing media on a broader scale.